Dynamic Analysis of Perioperative Hidden Blood Loss in Intertrochanteric Fractures - Tian, Shuwei (Clin Appl Thromb Hemost, 2019)
To analyze the dynamic variation in perioperative hidden blood loss in patients with intertrochanteric fracture. From January to December 2017, 79 patients with intertrochanteric fracture were treated with proximal femoral nail antirotation. Serial complete blood count assays were performed consecutively in the 3 days after admission, on the day of surgery, and 7 days postoperatively. Blood loss during surgery, postoperative drainage, and perioperative blood transfusion volumes were recorded. Dynamic changes in hemoglobin (Hb) prior to surgery were recorded and compared between males and females. Patients were divided into the no blood transfusion group, the 400-mL blood transfusion group, and the 800-mL blood transfusion group depending on the volume of perioperative blood transfusion. Total and hidden blood loss were separately calculated according to the Gross equation. Lowest mean Hb values occurred on day 2 after admission among men (104.8 g/L) and on day 3 after admission among women (98.6 g/L). The average Hb decrease was 11.4 g/L, 11.8 g/L, and 8.9 g/L in the no, 400-mL, and 800-mL blood transfusion groups, respectively. The lowest Hb value occurred on postoperative day 2. Hemoglobin increased on postoperative day 3 and stabilized by day 6. In the no blood transfusion group, the average total blood loss was 406.0 ± 255.6 mL, 628.3 ± 267.2 mL, and 759.7 ± 322.1 mL in the no blood transfusion, 400-mL blood transfusion, and 800-mL blood transfusion groups, respectively, and hidden blood loss was 326.0 ± 246.6 mL, 512.1 ± 247.3 mL, and 596.1 ± 306.9 mL, respectively. Perioperative hidden blood loss occurred prior to surgery for intertrochanteric fracture and ended on postoperative day 2.